2012
DOI: 10.1007/s00404-012-2260-3
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and depression: a case–control study in Tehran

Abstract: With regard to the high prevalence of moderate to severe depression and its association with preeclampsia, our findings support and suggest efforts for screening depression among pregnant women and appropriate educational studies for mental and psychological problems during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 16 publications
(26 reference statements)
1
25
0
8
Order By: Relevance
“…Among seven of these studies, five were positive [32][33][34][35][36] and two were negative; 21,23 since most did not inquire about the prepregnancy period, there is no way to know whether depression/anxiety symptoms and/or diagnoses during pregnancy represented a preexisting chronic problem. One exception was a study that used interview and prenatal records to ascertain depression/anxiety diagnosis during and prior to pregnancy and reported no association with PE for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Among seven of these studies, five were positive [32][33][34][35][36] and two were negative; 21,23 since most did not inquire about the prepregnancy period, there is no way to know whether depression/anxiety symptoms and/or diagnoses during pregnancy represented a preexisting chronic problem. One exception was a study that used interview and prenatal records to ascertain depression/anxiety diagnosis during and prior to pregnancy and reported no association with PE for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…29 Our results are higher than in most studies found in the literature. 22,26 The difficult social conditions of the populations could be the common feature of these studies. Preeclampsia will occur in women already in a precarious social situation.…”
Section: Discussionmentioning
confidence: 99%
“…For each item, we assigned a score of 0, 1, 2, and 3, to the response categories of 'not at all', 'several days', 'more Authors obtained the total by adding together the scores for the nine questions. With a possible total score of 27, patients were classified as absence of depression (PHQ-9 score: 0-4), mild depression (PHQ-9 score: 5-9), moderate depression (PHQ-9 score: 10-14), moderately severe depression (PHQ-9 score: 15-19), or severe depression (PHQ-9 score: [20][21][22][23][24][25][26][27]. At the end of it all, patients who scored ≥10 suggestive of anxiety as well as depressive disorders were referred for appropriate psychiatric care.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu és mtsai vizsgálati eredményei szerint a terhességük alatt mérsékelt depressziós tüneteket mutató nőknek 2,3-szer, a súlyo-sabb tüneteket mutatóknak 3,2-szer nagyobb kockáza-tuk volt a praeeclampsia kialakulására [29]. Kharaghani és mtsai kutatásában a középsúlyos, illetve súlyos depresszióval diagnosztizált nők 2,5-szer nagyobb valószí-nűséggel lettek praeeclampsiásak várandósságuk során [30]. Továbbá, az anya kór történetében szereplő koráb-bi pszichiátriai zavarok -különös tekintettel a depressziós és szorongásos kór képekre -szintén megnövelhetik a praeeclampsia kialakulásának esélyét [31].…”
Section: A Pszichés Faktorok Vizsgálata Praeeclampsiábanunclassified